2015
DOI: 10.1002/esp.3867
|View full text |Cite
|
Sign up to set email alerts
|

Salt marsh surface survives true‐to‐scale simulated storm surges

Abstract: A full-scale controlled experiment was conducted on an excavated and re-assembled coastal wetland surface, typical of floristically diverse northwest European saltmarsh. The experiment was undertaken with true-to-scale water depths and waves in a large wave flume, in order to assess the impact of storm surge conditions on marsh surface soils, initially with three different plant species and then when this marsh canopy had been mowed. The data presented suggests a high bio-geomorphological resilience of salt ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 35 publications
2
41
0
Order By: Relevance
“…In contrast to the highly variable bed levels on the tidal flats, the bed levels remained much more constant on the marshes (Figure ). Experimental results by Spencer et al () also showed highly stable bed levels on a marsh during high hydrodynamic energy conditions. Location 2E.…”
Section: Discussionmentioning
confidence: 82%
“…In contrast to the highly variable bed levels on the tidal flats, the bed levels remained much more constant on the marshes (Figure ). Experimental results by Spencer et al () also showed highly stable bed levels on a marsh during high hydrodynamic energy conditions. Location 2E.…”
Section: Discussionmentioning
confidence: 82%
“…Several studies indicate that coastal vegetation may reduce erosion both on bed load form and resuspension (Ward et al ; Christianen et al ; Spencer et al ), which is normally attributed to a reduction of the hydrodynamics within the canopy (Bos et al ; Infantes et al ; Möller et al ). The reduction of the sediment erosion is important to maintain the water clarity, necessary for seagrass development (Dennison ; Duarte ), and to retain the sediment in coastal areas (Christianen et al ; Ganthy et al ; Spencer et al ). Whereas a lot of work has focused on the aboveground plant‐flow interactions, the effect of belowground biomass (rhizomes and roots) on the sediment stabilization is still relatively poorly studied.…”
mentioning
confidence: 99%
“…In their discussion of intertidal mangrove forests, Balke and Friess (2016) offer a compelling argument for the application of geomorphological knowledge for successful restoration and conservation, and for improving coastal resilience against extreme storms in the tropics. Similarly, Spencer et al (2016) demonstrate how European saltmarsh communities show high resilience with respect to sediment erosion under true-to-scale simulated storm surge conditions. Their study further demonstrates how species' morphological traits moderate the nature and efficacy of biogeomorphological processes.…”
Section: Applied Biogeomorphologymentioning
confidence: 82%